(untitled) (The Agriculturists, 2012)
The experiment was conducted at the Research Farm of Crop Physiology and Ecology Department, Hajee Mohammad Danesh Science and Technology University, Dinajpur, Bangladesh during 14 August to 7 December, 2008 to study the effects of organic fertilizer on yield performance of five fine rice cultivars viz., Rajshahi Swarna, Silkumul, Kataribhog, Lal Pajam and Sanla. The experiment was laid out in a split plot design with three replications. Effective tillers hill-1, plant height, panicle length, filled grains panicle-1, total grains panicle-1, 1000-seed weight, grain yield, straw yield and harvest index (HI) were significantly influenced by the combined effect of cultural conditions and rice cultivars. Under inorganic and organic culture, the highest grain yield was obtained from Rajshahi Swarna (2.90 and 2.74 t ha-1, respectively) and the lowest were from Sanla (2.20 and 1.74 t ha-1, respectively). All the cultivars showed better performance in respect of grain yield and other parameters under inorganic culture than organic culture. DOI: http://dx.doi.org/10.3329/agric.v10i2.13146 The Agriculturists 2012; 10(2) 98-103